Breast angiosarcoma: case report (Research, Society and Development, 2020)
Primary breast sarcomas are neoplasms originating from the connective tissue of this region and correspond to less than 1% of all mammary malignancies. Primary angiosarcoma of the breast is extremely rare. The relative incidence in relation to breast sarcomas is 2.7 to 7.9%. The predominant clinical aspect is that of a painless breast mass, sometimes with diffuse breast enlargement. The overlying skin may be violet or black in color. It is classified into 3 categories, being: group I or well differentiated. Group II tumors, either intermediate or moderately differentiated - have more frequent mitotic activity; Finally, in group III or poorly differentiated are tumors that present areas of solid growth composed of spindle cells, with pronounced mitotic activity. The aim of this study was to demonstrate a case of breast angiosarcoma in a patient from a public hospital in Teresina – PI.Considering the rare incidence and delayed diagnosis described in the literature that interfere with the early initiation of adequate therapy, here is a case report occurred in our service.